3D T2‐weighted spin echo imaging in the breast. Issue 2 (17th April 2013) - Moran, Catherine J.; Hargreaves, Brian A.; Saranathan, Manojkumar; Lipson, Jafi A.; Kao, Jennifer; Ikeda, Debra M.; Daniel, Bruce L.
Abstract : Purpose: To evaluate the performance of 2D versus 3D T2‐weighted spin echo imaging in the breast. Materials and Methods: 2D and 3D T2‐weighted images were acquired in 25 patients as part of a clinically indicated breast magnetic resonance imaging (MRI) exam. Lesion‐to‐fibroglandular tissue signal ratio was measured in 16 identified lesions. Clarity of lesion morphology was assessed through a blinded review by three radiologists. Instances demonstrating the potential diagnostic contribution of 3D versus 2D T2‐weighted imaging in the breast were noted through unblinded review by a fourth radiologist. Results: The lesion‐to‐fibroglandular tissue signal ratio was well correlated between 2D and 3D T2‐weighted images (R 2  = 0.93). Clarity of lesion morphology was significantly better with 3D T2‐weighted imaging for all observers based on a McNemar test ( P  ≤ 0.02, P  ≤ 0.01, P  ≤ 0.03). Instances indicating the potential diagnostic contribution of 3D T2‐weighted imaging included improved depiction of signal intensity and improved alignment between DCE and T2‐weighted findings. Conclusion: In this pilot study, 3D T2‐weighted imaging provided comparable contrast and improved depiction of lesion morphology in the breast in comparison to 2D T2‐weighted imaging. Based on these results further investigation to determine the diagnostic impact of 3D T2‐weighted imaging in breast MRI is warranted.J. Magn. Reson. Imaging 2014;39:332–338 . ©2013 Wiley Periodicals, Inc .